The Rainbow fish - Pfister, Marcus (New York : North-South Books, 1995)
The most beautiful fish in the entire ocean discovers the value of inner beauty and friendship.
Translation of: Der Regenbogenfisch.
4.6
K-3
Keywords: Oversize books -- Specimens; Beauty, Personal -- Fiction; Fishes -- Fiction; Friendship -- Fiction; Oversize books; Big books; Fishes -- Fiction; Friendship -- Fiction; Personal appearance -- Fiction